Students' Level of Awareness on the Waste Contribution of the Fast Fashion with Their Clothing Consumption Behavior - Peña, Ma. Christiana B.; Cruz, Justine R. Dela; Cabral, Ray Angel Lyn B.; Ramos, Maria Rafaela T.; Basilio, Eleonor R. (International Journal of Environment, Engineering and Education, 2023)
The accessibility and convenience of purchasing fashion items have increased due to continuous manufacturing and high demand. The fast fashion industry has capitalized on the latest trends by offering cheap, affordable, yet disposable items, contributing to global pollution through solid waste and wastewater. This study aims to assess (a) students' level of awareness regarding the waste contribution of the fast fashion industry, (b) their clothing consumption behavior concerning purchases and utilization, (c) their waste disposal practices, and (d) the relationship between clothing consumption behavior and their level of awareness. The study employs systematic random sampling to determine an appropriate sample size from the student population, resulting in 104 student respondents for the adapted survey. Goodman and Kruskal's Gamma analysis assesses the association between clothing consumption and awareness. The results indicate that the students know about the industry's wastewater and solid waste contribution. However, the study also reveals a negligible to moderate relationship between clothing consumption, including the frequency of purchases and utilization, and their overall awareness. This suggests that despite being highly aware of the environmental issues associated with the fast fashion industry, students continue to support and purchase products from this sector.